Pemodelan fenologi populasi penggerek batang padi kuning Scirpophaga incertulas (Walker) berbasis pengaruh iklim - Koem, Syahrizal; Koesmaryono, Yonny; Impron, Impron (Perhimpunan Entomologi Indonesia, 2014)
Rice stem borer abundance are largely influenced by climate. This research aims to (i) develop a population dynamic model of yellow stem borer (YSB) and (ii) to assess the model's ability to predict abundance and population peak of YSB under climate change scenario SRES A1FI and B1. Modeling the YSB requires two major components: climate parameter and lower developmental threshold temperatures (To) to describe life cycle of YSB from the egg, larva, pupa, and adult stages. The research utilized DYMEX software to describe development, mortality, transfer of individuals from one to the next life stages, fecundity and reproduction of YSB. The coefficient of determination (R2) of calibration models between predictions and observations showed a strong positive correlation of 0.65. Model validation could well predict the peak population, with R2 = 0.42. The simulations showed that the trend of population peak occur at high rainfall i.e. in March to April, July to September, and November to December. The model predicted YSB population in the Sukamandi reaches 3 generations per year, while in Kuningan 2 generations per year. Simulation models under climate change scenarios SRES A1FI and B1 showed differences in the sensitivities. Trend of YSB population is increasing in the regions Kuningan and decreasing in region Sukamandi. Under changing climate, environment conditions in Kuningan become more suitable for the proliferation of YSB, allowing an increase in the number of generations per year.